Breeding for public health: A strategy. (October 2018) - Hansson, Sven Ove; Åman, Per; Becker, Wulf; De Koning, Dirk-Jan; Lagerkvist, Carl Johan; Larsson, Ingrid; Lehrman, Anna; Risérus, Ulf; Stymne, Sten
Abstract: Background: Plant and animal breeding can contribute to promote human health by providing new and healthier food products that farmers can produce in an economically viable way and consumers will choose to buy and eat. However, this can only be achieved if breeding makes full use of knowledge about nutrition, consumer behaviour, farming and agricultural economics. A strategy is needed for breeding for public health. Scope and Approach: A multidisciplinary group of researchers has developed a strategy for plant and animal breeding for public health. The group includes experts in plant breeding, animal breeding, food science, nutrition science, clinical nutrition, agricultural economics, consumer research, and ethics. Key Findings and Conclusions: An outline is proposed of a strategy for breeding for public health. It aims at improving public health in both low- and high-income countries. To prevent chronic disease, the highest priority should be to develop healthy variants of traditional food items that can be introduced universally, i.e. completely replace the older, less healthy variants. In particular in low-income countries, food products with enhanced micronutrient content are urgently needed. In all countries, crops with improved fatty acid composition can contribute substantially to improved public health. A reasonable second priority is products that may not be suitable for universal introduction but will expectedly be demanded by large groups of consumers. One example could be diminishing the energy density of traditional foodstuffs by reducing their fat, sugar, and starch content and increasing their dietary fibre content. Changes in the current organization of the market for farm products are needed to encourage the production of healthier foodstuffs. Highlights: A strategy is proposed for breeding for public health. The first priority is healthy products that can be introduced universally. The second priority is other healthy products with expected consumer demand. Oils and fats with improved fatty acid composition exemplify the first priority. Crops with lower energy density and more dietary fibre exemplify the second priority.